(untitled) (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في مشفى الأسد الجامعي في اللاذقية في قسم التوليد وأمراض النساء في الفترة الواقعة بين 1/1/2003 و1/6/2004. وتضمنت مائة ماخض تم وضعهن في غرفة مجهزة بتلفاز (أفلام عربية اجتماعية) لدراسة دور المؤثر البصري في تخفيف آلام المخاض عندهن. تم تقييم شدة الألم من خلال مقياسين للألم هما: المقياس الشفهي البسيط والمقياس السلوكي بالدراسة تبين: 1- للتلفاز (بوصفه مؤثرا بصريا) دور هام في تخفيف آلام المخاض وذلك بغض النظر عن العمر والحالة الولادية للماخض. 2- كان تأثير التلفاز في تخفيف آلام المخاض عند الخروسات أكبر منه عند الولودات وعديدات الولادة. 3- كان تأثير التلفاز في تخفيف آلام المخاض عند الفئات العمرية الصغيرة <18 سنة أكبر منه عند الفئات العمرية الأكبر سنا. The Research was Conducted in AL_ASSAD university Hospital, Lattakia, in Obstetrics and Gynecology department between 1/1/2003 and 1/6/2004, and included (100) pregnant woman in labor, put in a room with T.V (social Arab film), to study the role of (T.V) in minimizing the labor pain. The pain was evaluated by two standards: simple verbal and behavioral standard. By study: 1-T.V has an important role in minimizing labor pain regardless of the age or multi parity. 2-T.V has more effects in minimizing labor pain in prim gravidas than multiparities. 3-T.V has more effect in minimizing labor pain in small age categories (<=18 years) than the older ones.